Estudo da peroxidação lipídica in vivo e in vitro em ratos infectados experimentalmente com Trypanosoma evansi - Wolkmer, Patricia (2009)
The present study aimed to assess the lipid peroxidation and the susceptibility of erythrocytes in vitro peroxidation as indicators of oxidative damage in erythrocytes and its role to the pathogenesis of anemia during the early acute phase of Trypanosoma evansi infection in rats. Fifty male Wistar rats were randomly allotted into seven groups: three trypanosome-infected groups (T2, T4 and T6; n = 10 animals per group) and four uninfected controls (C0, C2, C4 and C6; n = 5 animals per group). Animals from trypanosome-infected groups were intraperitoneally injected with 106 trypanosomes. Blood sample was collected by cardiac puncture before infection (day 0; Group C0) or on the 2nd (C2 and T2), 4th (C4 and T4) and 6th (C6 and T6) day pos-infection (dpi). The number that follows the group name is referring to the day of the cardiac blood collection. The samples were analyzed for red blood cell count (RBC), hemoglobin (Hb) concentration, packed cell volume (PCV), plasma malondialdehyde (MDA) and in vitro peroxidation of erythrocytes. The mean values of the hematological indices gradually decreased in infected compared with the control rats. MDA was significantly increased (P < 0.001) on 6th dpi in infected versus controls and was negatively correlated with PCV (P < 0.001; R² = 0.372). The erythrocytes in vitro peroxidation values were higher in group T4 and T6 than control rats (P < 0.01). There was positively correlation with erythrocytes peroxidation (P < 0.001; R² = 0.414) and MDA. The results of this study indicate that T. evansi infection in rats is associated with oxidative stress, indicated by lipid peroxidation, and oxidative damage in erythrocytes membrane, as demonstrated by in vitro peroxidation. This may be one of the causes of anemia in acute trypanosomosis.